Insurers' investment behaviour and the coronavirus (COVID-19) pandemic - Constanze Fay; Angelica Ghiselli (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2023)
This research explores two aspects of European insurers' investment behaviour related to crises. While they are often considered as financial market stabilisers and long-term investors, there is currently a lack of knowledge about insurers' investment behaviour in crises under the regulatory Solvency II regime implemented in 2016. With assets of nearly exteuro9 trillion and bond holdings of more than exteuro3 trillion in Q2 2022, European insurers are important financial intermediaries and finance European economies. With an empirical study, we investigate their reaction to the asset price shock at the onset of the coronavirus (COVID-19) pandemic in the first quarter of 2020 and explore cyclical investment behaviour by replicating Timmer's (2018) study with fixed effects panel regressions. We use a large cross-country dataset, with the novelty of exploiting cross-country heterogeneity for European countries with 458,758 security-level observations from 2017 to 2022. Overall, our findings are very relevant from a policy perspective as they suggest active and heterogeneous cyclical investment behaviour in the European insurance market with differences across issuer and holder countries of domicile.
Keywords: G01; G11; G15; G22; G28; 330; Insurance Companies; Cyclicality; Portfolio Allocation; Financial Stability; Pandemic; Debt Capital Flows